2020
DOI: 10.1590/1678-9199-jvatitd-2019-0047
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of nanogold conjugated toxin GNP-NN-32 from Naja naja venom

Abstract: Background: Cancer is the second most common fatal disease in the world, behind cardiovascular disorders in the first place. It accounts for around 0.3 million deaths per year in India due to the lack of proper diagnostic facilities, prevention and treatment. Current therapeutic methods do not provide adequate protection and affect normal cells along with cancerous ones. Thus, there is a need for some alternative therapeutic strategy, preferably from natural products, which have been traditionally used for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…The growing popularity of CuS nanoparticles in the field of biosensing is primarily based on conductivity and capacity of these nanoparticles, which encourage electron transfer reactions with molecules. Furthermore, CuS thin filmbased immunosensor was introduced for the exposure of anthropological immunoglobulin A (IgA) antibody in serum, in which a goat antihuman IgA antimediator was immobilized on surface of CuS thin film (Attarde and Pandit, 2020). The functionalized quantum dots of Ag 2 S are also important to use in bioimaging and diagnostics purposes.…”
Section: Metal Sulfide-based Nanoparticlesmentioning
confidence: 99%
“…The growing popularity of CuS nanoparticles in the field of biosensing is primarily based on conductivity and capacity of these nanoparticles, which encourage electron transfer reactions with molecules. Furthermore, CuS thin filmbased immunosensor was introduced for the exposure of anthropological immunoglobulin A (IgA) antibody in serum, in which a goat antihuman IgA antimediator was immobilized on surface of CuS thin film (Attarde and Pandit, 2020). The functionalized quantum dots of Ag 2 S are also important to use in bioimaging and diagnostics purposes.…”
Section: Metal Sulfide-based Nanoparticlesmentioning
confidence: 99%
“…Pegylated gold nanoparticles (PEGAuNPs, 24 nm, 9.8 nM) combined with chemotherapy drugs (doxorubicin or varlitinib) also have a very good cytotoxic effect on pancreatic cancer cells [ 49 ]. Toxin from Naja naja venom (NN-32, IC50: 5.0 µg/mL) combined with gold nanoparticles (18 nm) increased the percentage of cytotoxic activity and apoptosis of two human breast cancer cell lines (MCF-7 and MDA-MB-231) [ 50 ].…”
Section: Cancermentioning
confidence: 99%
“…Several previous studies have reported the occurrence of muscle fiber degeneration after the injection of cardiotoxin from N. atra [44][45][46], which is similar to the pathological analysis results of heart tissue obtained in the present study. The study of Naja venom is important due to its great potential for medical application as an anticancer among others [47].…”
Section: Discussionmentioning
confidence: 99%